The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.4103/0970-0358.59283
|View full text |Cite
|
Sign up to set email alerts
|

Lip adhesion revisited: A technical note with review of literature

Abstract: Context (Background):Lip adhesion is a direct edge approximation without changing lip landmarks or disturbing tissue required for definitive closure. This converts a complete cleft into an incomplete cleft, facilitating and enhancing subsequent definitive lip and nose repair.Aim:The study aims to describe our technique of lip adhesion and its morbidity, and discuss the rationale for its use.Settings and Design:Retrospective follow-up study of complete clefts operated upon in the Bruges Cleft and Craniofacial C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…16 In addition, reported rates of dehiscence can be as high as 24% in bilateral cases and 8% in unilateral cases. 17,18 Fortunately, no patients in our study experienced any of these complications; however, the complication risk profile is not inconsequential, and should be carefully weighed against the potential benefit on a case-bycase basis. We believe that the procedure should only be offered to patients with very wide clefts to limit the amount of soft tissue undermining, as undermining may potentially negatively impact maxillary growth.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…16 In addition, reported rates of dehiscence can be as high as 24% in bilateral cases and 8% in unilateral cases. 17,18 Fortunately, no patients in our study experienced any of these complications; however, the complication risk profile is not inconsequential, and should be carefully weighed against the potential benefit on a case-bycase basis. We believe that the procedure should only be offered to patients with very wide clefts to limit the amount of soft tissue undermining, as undermining may potentially negatively impact maxillary growth.…”
Section: Discussionmentioning
confidence: 80%
“… 16 In addition, reported rates of dehiscence can be as high as 24% in bilateral cases and 8% in unilateral cases. 17 , 18…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of Logan bow cite reduced incisional tension, protection of the upper lip from direct trauma while allowing easy access for wound care, and the ability to maintain dressings in place as reasons for using the device, but offer little to no objective evidence. 10 - 13 Some authors have reported using the device after cleft lip adhesion 14 while others have described preoperative use of Logan bow in hopes of reducing lip tension at the time of definitive cheiloplasty. 15 There are no formal reports of complications or adverse events associated with the use of Logan bow, although Logan himself noted irritation of the cheek skin as a potential problem.…”
mentioning
confidence: 99%